BUMDes Syariah sebagai Solusi Pembangunan Perekonomian Syariah Desa yang Berkeadilan - Sundari Sundari; Syarifudin Syarifudin (IQTISHODUNA, 2022)
Along with the times, many sharia products have started to appear, ranging from food, fashion trends in clothing, make-up, to not forgetting to take part in the development of BUMDes. These concepts are very strategic in building Islamic economics and finance. This article aims to analyze the equitable distribution of BUMDes economic development by implementing the sharia system in it. The Library Research method is used to strengthen facts to compare the differences and/or similarities between the theory and practice that the researcher examines. This study shows that with the existence of BUMDes, very few use the sharia system and more use the conventional system. In fact, the village community has carried out daily economic activities using a profit-sharing system such as maro, gadoh, profit-sharing, livestock revenue-sharing, and others. This system was formed by them because the profit-sharing system has a fairer value and transparency for the businesses they have run so far. In addition, the researcher also found that the seasonal murabahah financing system is very appropriate considering the large number of BUMDes members who work as farmers in the village.